HUBUNGAN PENGETAHUAN, STATUS GIZI, DAN SANITASI LINGKUNGAN DENGAN KEJADIAN ISPA PADA ANAK PUSKESMAS PARUNG PANJANG - Happy Novriyanti purwadi; Intan Maharany; Dieta Nurrika; Dwi Astuti Sih Apsari; Desi Rusiana Alfiani (LPPM STIKes BHAKTI HUSADA CIKARANG, 2026)
Background: Acute Respiratory Infection (ARI) remains one of the major health problems among children with a high incidence rate in Indonesia. Several factors may influence the occurrence of ARI in children, including maternal knowledge, nutritional status, immunization status, history of exclusive breastfeeding, presence of smokers, use of mosquito coils, and household cleanliness. Data from the working area of Parung Panjang Health Center indicate an increasing trend in ARI cases among children from year to year, highlighting the need to identify risk factors associated with ARI incidence. Objective: This study aimed to determine the relationship between knowledge, nutritional status, and environmental sanitation with the incidence of Acute Respiratory Infection (ARI) among children at Parung Panjang Health Center in 2025. Methods: This study employed a quantitative research design with a descriptive-analytic cross-sectional approach. A total of 107 respondents were selected using purposive sampling. Data were collected through structured questionnaires and analyzed using the Chi-square test and Fisher's Exact Test. Results: The findings revealed that nutritional status had a significant relationship with the incidence of ARI among children (p = 0.017). Meanwhile, maternal knowledge (p = 0.407), and household cleanliness (p = 1.000) were not significantly associated with the incidence of ARI. Conclusion: Nutritional status is a significant factor related to the incidence of ARI among children. Strengthening nutritional monitoring and health education programs is recommended to reduce ARI cases among children. Keywords: Acute Respiratory Infection, nutritional status, environmental sanitation